2020
DOI: 10.1007/s40653-020-00323-z
|View full text |Cite
|
Sign up to set email alerts
|

Faith-Based Medical Neglect: for Providers and Policymakers

Abstract: A substantial minority of Americans have religious beliefs against one or more medical treatments. Some groups promote exclusive reliance on prayer and ritual for healing nearly all diseases. Jehovah's Witnesses oppose blood transfusions. Hundreds of thousands of schoolchildren have religious or conscientious exemptions from immunizations. Such exemptions have led to personal medical risk, decreases in herd immunity, and outbreaks of preventable disease. Though First Amendment protections for religious freedom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…According to this worldview, human beings are the image of God (who is spiritual) and therefore cannot be sick (which is a material phenomenon). However, sin, ignorance of God, and fear—including fear of disease induced by a doctor's visit—may cause disease, and the only remedy is prayer and a correct mindset, that is, convincing oneself that the disease is a delusion [16] , [17] .…”
Section: Resultsmentioning
confidence: 99%
“…According to this worldview, human beings are the image of God (who is spiritual) and therefore cannot be sick (which is a material phenomenon). However, sin, ignorance of God, and fear—including fear of disease induced by a doctor's visit—may cause disease, and the only remedy is prayer and a correct mindset, that is, convincing oneself that the disease is a delusion [16] , [17] .…”
Section: Resultsmentioning
confidence: 99%
“…In a longitudinal study, Pargament and Koenig [ 35 ] found that in elderly patients, an illness accompanied with religious distress (feeling punished by God or angry towards God, or feeling the devil was at work) was associated with a higher risk of mortality. Rosenbaum [ 36 ] discusses objections to contraception on religious grounds, and Swan [ 37 ] analyses a range of religious beliefs against medical treatments, including blood transfusions, open heart surgery, immunizations, prevention, and screening procedures. D’Souza [ 38 ] asserts that although clinicians should be objective, keeping their religious beliefs separate from their own practice, by doing so, they should not stray into dissociating patients’ beliefs and spiritual needs from their care.…”
Section: Introductionmentioning
confidence: 99%